A new topology of non-isolated AC-DC quadratic boost converter with enhanced power traits - Ahmed, Istiak; Azad, Ferdous S.; Hasan, Shameem; Al Mamun, Abdullah; M. Salim, Khosru (Institute of Advanced Engineering and Science, 2024)
A novel AC-DC quadratic boost converter (QBC) topology is presented in this paper which can provide higher power factor (PF), lower total harmonic distortion (THD) and higher voltage when compared to a conventional AC-DC boost convertero This is achieved by using additional switched capacitor and switched inductor in the power processing stage. The presented converter is analyzed theoretically, and a voltage gain equation is derived. A simulation model is created to evaluate the converter performance under various duty cycles, switching frequency, and changing output load. The input PF, THD, and voltage gain of the simulated model were compared with conventional converter to determine the validity of the suggested converter circuit. The results show that the efficiency, PF, THD and voltage gain value reaches approximately 97.9%, 0.98, 16.14, and 2.83 respectively at a duty cycle of 50% with fixed output load of 100 Ω. A dual loop voltage and current controller is also arrayed with the proposed circuit which allows further enhancement in PF (0.997) and THD (7.45%). This converter can be a suitable option for systems where isolation is not necessary but high PF, high voltage gain and low THD are required.